Implementation of a Web-Based Agricultural Management Information System with Integrated Operational and Financial: A Case Study at Okazakki Farm - Lahan Adi Purwanto; Feri Wibowo; Ridho Muktiadi; Akhul Isyfa Rhamdani (Politeknik Piksi Ganesha Indonesia, 2026)
Operational management in small and medium-scale agricultural enterprises is commonly conducted manually, leading to inaccuracies in record-keeping, limited traceability of cultivation cycles, and inconsistencies in financial reporting. This study aims to develop a web-based agricultural management information system that integrates planting, harvesting, labor management, and financial processes at Okazakki Farm. The system was developed using the Rapid Application Development method with iterative prototyping, while system requirements were collected through observation, interviews, and documentation. The system was implemented using a web-based framework and a relational database. The implementation results demonstrate that the system is capable of validating field block availability, recording harvest activities along with associated labor, updating inventory levels, and automatically generating income and expense records. Black-box testing results indicate that all core system functionalities operate in accordance with user requirements. This research contributes to supporting the digitalization of agricultural enterprises through end-to-end integration of operational and financial processes.